Implikasi Yuridis Tata Kelola Perizinan Usaha Berbasis Risiko terhadap Asas Otonomi di Indonesia - Moh Syafakhorrahman; Mushafi Miftah (AHKAM, 2025)
This study is motivated by the limited scholarly attention given to the implications of the risk-based business licensing system on regional autonomy, despite its significant impact on the structure of decentralized governance in Indonesia. The aim of this research is to analyze the legal framework and juridical implications of the risk-based licensing system in relation to the principle of autonomy as enshrined in the Indonesian Constitution. A qualitative normative research design was employed, utilizing secondary legal materials selected through purposive sampling. Data were collected through literature review and document analysis, and examined using statutory, conceptual, and historical approaches. The findings reveal that the governance of risk-based licensing, as regulated by Government Regulation No. 28 of 2025, tends toward centralization and diminishes the authority of local governments, thereby conflicting with the principles of decentralization mandated by Law No. 23 of 2014 and the 1945 Constitution. This system is assessed as potentially weakening regional autonomy and creating opportunities for manipulation in risk assessment, which could lead to corrupt practices. The study concludes that a reformulation of licensing policy is needed to maintain a balanced distribution of authority between central and regional governments, while promoting transparency and accountability in public service delivery. The implications of this research include a theoretical contribution to the discourse on central–regional relations within a unitary state, and practical recommendations for revising the legal framework on licensing, strengthening local government capacity, and evaluating the implementation of digital platforms such as OSS-RBA within the context of decentralization.